Automation of a Lathe to Increase Productivity in the Manufacture of Stems of a Metalworking Company - Varela-Aldás, José (2020)
This project performs the optimization of the process for the manufacture of stems for the gas passage valves produced by the company INDUMETAL M&M, the problem is generated in the process of the elaboration of stems due to the lack of machinery for perform the machining of sufficient stems, the process had a working productivity of 59 units processed/hour of production of stems, which were not sufficient to meet the production requirement, so it was proposed to implement an automated system that solve the problem of production deficiency in the area of stems. The proposal was to reinvigorate the semi-automatic lathe Hardinge AHC (TH-05) existing in the area in very bad conditions, which occupied physical space and could fulfill the required work. For the implementation, a Programmable Logic Controller (SIEMENS S7 1200 PLC) and a Human Machine Interface (HMI DELTA) are used, increasing productivity to 89 units processed/hour of stems, fulfilling the objective set. © 2020, Springer Nature Switzerland AG.